Silenced: Palestinian Families in Berlin Navigating Increased Censorship and Surveillance - Carola Tize (Genealogy, 2025)
The 7 October 2023 attack by Hamas on Israeli civilians and Israel’s ensuing assault in Gaza caused immense public upheaval in Berlin, home of Europe’s largest Palestinian diaspora. This article shows how Palestinian families intergenerationally navigate the ensuing losses, protests and school unrests, which took place not just in response to the devastation in Gaza and the West Bank, but also to Germany’s unwavering support for Israel, while suppressing pro-Palestinian voices. For the families, this intensification of the protracted Israeli–Palestinian conflict deepened a state of chronic crises based on traumas, longstanding insecurity and increasing xenophobia in Germany. Drawing from 11 years of ethnographic research in Berlin–Neukölln, I show how events since 7 October drastically changed the neighborhood’s ethos, forcing a communal front of silence. The silence was a reaction to fears of being misrepresented in the media and threats of deportation and school expulsions. Examining prevailing sociopolitical influences, and what happens within families and between generations, I illustrate how families became more insular in their mourning and grief yet found ways to navigate their political views intergenerationally. My argument scrutinizes sociopolitical processes leading to increased polarization and highlights the importance of schools as safe spaces for identity formation and contemplation.